Fabrication and Sensing Applications of Multilayer Polymer Optical Waveguides. (2016) - Rezem, Maher; Günther, Axel; Rahlves, Maik; Roth, Bernhard; Reithmeier, Eduard
Abstract: For sensing applications in structural health monitoring, process technology or life sciences polymer micro-optical sensors are highly promising as they offer several advantages in comparison to other sensor types. In this work, a fabrication process of low-cost planar polymer optical waveguides based on hot embossing and doctor blading is presented. Such waveguides represent one of the main building blocks of micro-optical systems. The refractive index and propagation losses of several waveguide materials are characterized. In order to increase the integration density of optical components, the fabrication of multilayer waveguides is investigated. Finally, potential applications of the fabricated waveguides are outlined.